The caspian basin’s energy policy - YALÇINKAYA, ALAEDDİN (Cambridge Scholars Publishing, 2022)
Although the issue of energy is extremely important for the Caspian region, this region also constitutes an important crossroads of global and regional policies. In this context, which issues direct energy relations or which Caspian region problems actually arise from oil or gas politics is a controversial topic. The status of the Caspian, South Caucasus corridor, gas or oil pipelines, Nagorno-Karabakh conflict, Azerbaijan-Armenia-Turkey relations, Azerbaijan-Iran relations and Georgia-Russia relations are some of these issues. This chapter will focus on problems directly related to Caspian oil and gas. Other issues could be addressed in relation to these resources.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)